Assessment of knowledge towards emergency contraceptives among college students in Ramechhap district of Nepal - Pokharel, Yagya Raj; Pokharel, Shaluja; Shrestha, Bharat Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: A high rate of unintended pregnancy exists among college students as they belong to the sexually active age group. So, it is significant to know the knowledge of college students regarding emergency contraceptives. The objectives were to assess the knowledge of students towards emergency contraceptives and to identify the association between male and female students towards knowledge of emergency contraceptives. Method: An online survey in Ramechhap district among college students studying in bachelor’s and master’s level was conducted from March 15, 2022 to April 10, 2022 where total of 169 students participated. Non parametric test was used to find the result of the objectives. Result: The study showed that 83.4% students had the knowledge of Emergency Contraceptive pills and 59.2% of students first heard about such pills in the last 5 Years. Among them 79.9% of students knew where to get Emergency Contraceptive pills, 24.2% of students know the Emergency Contraceptive pills works if there is menstrual delay. Only 56.9% of students know the time to take Emergency Contraceptives pills after unprotected sexual intercourse and 46.7% of students know that the Emergency Contraceptive pill is not used for regular contraception. Only 49.1% of students know the right number of tablets that needs to be consumed after unprotected intercourse. Conclusion: Majority of the students are aware of the Emergency Contraceptive pills however they have limited understanding about it. In comparison to female students, male had better understanding about Emergency Contraceptives.